Optically Induced Calcium-Dependent Gene Activation and Labeling of Active Neurons Using CaMPARI and Cal-Light - Ebner, Christian; Ledderose, Julia; Zolnik, Timothy A.; Dominiak, Sina E.; Turko, Paul; Papoutsi, Athanasia; Poirazi, Panayiota; Eickholt, Britta J.; Vida, Imre; Larkum, Matthew E.; Sachdev, Robert N. S. (Frontiers in Synaptic Neuroscience, 2019)
The advent of optogenetic methods has made it possible to use endogeneously produced molecules to image and manipulate cellular, subcellular and synaptic activity. It has also led to the development of photoactivatable calcium-dependent indicators that mark active synapses, neurons and circuits. Furthermore, calcium-dependent photoactivation can be used to trigger gene expression in active neurons. Here we describe two sets of protocols, one using CaMPARI and a second one using Cal-Light. CaMPARI, a calcium-modulated photoactivatable ratiometric integrator, enables rapid network-wide, tunable, all-optical functional circuit mapping. Cal-Light, a photoactivatable calcium sensor, while slower to respond than CaMPARI, has the capacity to trigger the expression of genes, including effectors, activators, indicators or other constructs. Here we describe the rationale and provide procedures for using these two calcium-dependent constructs (1) in vitro in dissociated primary neuronal cell cultures (CaMPARI & Cal-Light); (2) in vitro in acute brain slices for circuit mapping (CaMPARI); (3) in vivo for triggering photoconversion or gene expression (CaMPARI & Cal-Light); and finally, (4) for recovering photoconverted neurons post-fixation with immunocytochemistry (CaMPARI). The approaches and protocols we describe are examples of the potential uses of both CaMPARI and Cal-Light. The ability to mark and manipulate neurons that are active during specific epochs of behavior has a vast unexplored experimental potential.